Tips and Tricks in Molecular Imaging - Ali Tarighatnia; Gurkaran Johal; Ayuob Aghanejad; Hossein Ghadiri; Nader D. Nader (Frontiers in Biomedical Technologies, 2021)
A variety of imaging modalities include X-ray-based Computed Tomography (CT) scan, Ultrasound (US), Magnetic Resonance Imaging (MRI), Nuclear Medical Imaging (NMI), and Optical Imaging (OI) are used to help diagnose and treat diseases through anatomical, physiological, and functional representation. With the advent of molecular imaging using nanoparticles, detailed information about properties is provided and facilitates early detection of malignancies. Now, novel approaches in nanoparticle designing, the development of hybrid imaging modalities, and improvements in the sensitivity of instruments have raised the level of disease diagnosis.